Community and specific-species level responses to environmental conditions of the snakes of a coastal dune ecosystem in subtropical Brazil inferred from a nine years temporal gradient - Iglesias, Marco Miguel Odicio (2022)
Ecologist may intuitively think that responses to disturbances at the population level scale up to impact community-level properties. However, there is experimental and empirical evidence suggesting that large magnitude responses to disturbances observed at the population level do not necessarily translate into equivalent changes at the community level. We investigate if snake community composition and the abundance of specific-species change across the time and if this change could be explain by environmental conditions, at the same time, we see if both community and population has equivalent responses, to those changes. To this, we work in a same local of coastal dunes ecosystem (<444 hectares) in a temporal scale, between 1998 – 2004 and 2020 -2021. Our results show that community and four species of snake decreased across time. The reduction of community composition was in the last periods (2020-2021) when was compared 15 years ago, with the las period of 2004. At community level, environmental variable explains a few variances of composition, whereas positive temporal correlation act as a dominant factor, suggesting that reduction on community cannot be explain by environmental models. At population level, we detected a confirm case of decreased in the snake Xenodon dorbignii and negative tendency on decreased of three species. Overall, environmental variables were positively correlated with the abundances, and cannot explain the decreased patron on snakes. In coastal sand dunes, both community and population responses in the same way.